Generation of optical vortices in rotating uniaxial crystal for light propagation along the perpendicular to its optical axis - Sokolenko, B.V.; Rubass, A.F.; Volyar, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We have experimentally considered evolution of the Gaussian beam
propagating nearly perpendicular to the uniaxial crystal axis. Also we have analyzed the
spin and orbital angular momenta and found oscillations of the angular momentum when
the crystal optical axis is rotated.